Macular Microvasculature Density Changes in Anisometropic Amblyopic Eyes after Successful Treatment - Wuhe Chen; Frank Thorn; Ruzhi Deng; Xiaoman Li; Jiangtao Lou; Yingjie Wang; Xinping Yu (Journal of Ophthalmology)
Purpose. To determine if the abnormal macular microvasculature in hyperopic anisometropic amblyopia changes after occlusion therapy, and to discover if the macular microvasculature influences the efficacy of amblyopic treatment. Materials and Methods. Twenty-two children with hyperopic anisometropic amblyopia (median, 8 years old) were enrolled along with 66 healthy controls of similar age and gender distribution. Best-corrected visual acuity (BCVA) was determined, and macular vessel density in the superficial and deep capillary plexuses (SCPs and DCPs, respectively) was measured by optical coherence tomography angiography before and after refractive correction and occlusion therapy. Changes in BCVA and macular SCP and DCP vessel density were measured after amblyopia treatment of 7.5 ± 4.4 months. Results. The amblyopic baseline BCVA, logMAR 0.42 ± 0.27, improved to logMAR 0.18 ± 0.18 in 14 patients (64%) after amblyopia treatment (P<0.001). In 8 patients (36%), there was no improvement in the BCVA. In amblyopic eyes with improved BCVA, the SCP density tended to increase in each parafoveal quadrant, while it tended to decrease in all quadrants of the fellow eyes. For patients in whom BCVA did not improve, the macular SCP vessel density tended to decrease in all quadrants of the amblyopic and fellow eyes. The posttreatment difference in SCP vessel density between amblyopic and fellow eyes was not significant. Multiple linear regression analysis showed that older age and greater foveal SCP vessel density were negatively correlated with BCVA improvement (P<0.018 and P<0.036, respectively). Conclusions. Macular vessel density tends to increase in anisometropic amblyopic eyes after successful treatment. Younger age and lower SCP macular density are predictive of a greater therapeutic effect of occlusion therapy.